The equations we are given are:

Equation 1 - 5x - 125 = Z - 3y

Equation 2 -Sqroot(Z-3y) = Sqroot(5x) - 5

Squaring Equation 2 we get:

Equation 3: z - 3y = 5x - 10sqroot(5x) + 25

Substituting equation 1 into 3 we get:

5x - 125 = 5x - 10sqroot(5x) + 25 ---------> x = 45

We are asked to determine the value

Sqroot((45(Z-3y)/x))

X = 45 so it cancels out with the 45 in numerator.

Therefore only Sqroot(Z-3y) remains.

From Equation 2 we know that Sqroot(Z-3y) = Sqroot(5x) - 5

Since x = 45 ---> Sqroot(5* 45 ) - 5 = 10

_________________

Migatte no Gokui